The Influence of Emotional Intelligence on Work Motivation. An Empirical Assessment (International Journal of Scientific Research and Management (IJSRM), 2021)
The paper investigated the association between emotional intelligence and work motivation among employees of organisations to determine whether emotional intelligence differences exist in work motivation, and to assess the nature of the association between emotional intelligence and work motivation. A sample of 140 respondents was selected through the convenience sample method for the primary data collection. A set of questionnaires developed by the researcher was used to collect data from the respondents. Data collected were analysed using descriptive and inferential statistics, and presented in Tables. The results indicate respondents are emotionally intelligent and are also motivated. The research findings also indicate emotional intelligence differences exist in work motivation. It is recommended that improvement in skills in the emotional intelligence of employees will contribute positively to work motivational levels, and organisation’s productivity, and growth. Organisations should, therefore, thrive to identify factors that improve the work motivation of employees.